1987
DOI: 10.2176/nmc.27.56
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Intracranial Mycotic Aneurysm associated with Acute Subdural Hematoma

Abstract: A case of ruptured intracranial mycotic aneurysm associated with acute subdural hematoma is presented. A 26-year-old woman with cardiac valve disease who had been intermittently febrile for 2 weeks suddenly became comatose. There had been no head injury. At the time of admission, a cardiac murmur was audible and petechiae were noted on the conjunctivae and fingers, suggesting a diagnosis of bacterial endocarditis. The blood culture yielded Streptococcus faecalis. The computed tomo graphic scan revealed an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…3) Trapping and excision have also been used for aneurysms located at different cortical segments of the MCA. 1,6,11,12,15,17) In the present case, preoperative angiographic assessment of the location and shape of the aneurysm suggested the lesion could have been due to mycotic infection, neoplasm, or arterial dissection. In addition, the lesion was located in the central artery of the MCA.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…3) Trapping and excision have also been used for aneurysms located at different cortical segments of the MCA. 1,6,11,12,15,17) In the present case, preoperative angiographic assessment of the location and shape of the aneurysm suggested the lesion could have been due to mycotic infection, neoplasm, or arterial dissection. In addition, the lesion was located in the central artery of the MCA.…”
Section: Discussionmentioning
confidence: 58%
“…Review of the 15 reported cases of aneurysms located at the cortical segment of the MCA showed that 14 cases resulted from infection and one occurred secondary to arterial dissection. 1,2,[5][6][7][9][10][11][12][15][16][17]19,20) Several surgical strategies for the treatment of distal MCA aneurysms have been reported. The first choice of the treatment for cerebral aneurysms is neck clipping, but this procedure is performed only for aneurysms located at the M 2 or M 3 segment of the MCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]12,14,18,24,25,29) The incidence of acute SDH related to ruptured cerebral aneurysms is 0.3-7.9%. 5,10) Collectively, the incidence of ruptured infectious aneurysm associated with acute SDH should be extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…19,30) However, ruptured intracranial infectious aneurysm manifesting as acute subdural hematoma (SDH) is quite rare, with only nine cases previously reported. [1][2][3]12,14,18,24,25,29) We treated a 21-year-old female with a ruptured distal middle cerebral artery (MCA) aneurysm presenting as ICH and SDH thought to be infectious in origin.…”
Section: Introductionmentioning
confidence: 99%